Characteristics of Congenital Clasped Thumb: A Case Report and Literature Review - Kim, Sungmin (Front Pediatr, 2021)
Congenital clasped thumb is a progressive flexion and adduction deformity presenting with heterogeneous congenital abnormalities and syndromes. This deformity is usually accompanied by first web space narrowing and metacarpophalangeal joint (MPJ) laxity. Understanding the various features of the clasped thumb and making an accurate diagnosis is essential for treatment. Depending on the classification, treatment can vary from conservative to surgical. We describe the case of a bilateral clasped thumb with various characteristics, which were treated differently according to the disease type. The deformity of the clasped thumb was bilateral, and the patient had MPJ flexion deformity, flexor pollicis longus shortening, first web space narrowing, and MPJ instability, which were confirmed through a stress test. The left thumb was a complex type and was surgically treated, whereas, the right thumb was a flexible type, which was treated with splinting; the treatment showed promising results at 2 years post surgery. Diagnosis of the clasped thumb through thorough history taking, physical examination and considering its characteristics, and appropriate classification of the disease is essential for treatment. Furthermore, a stress test can identify MPJ instability in the congenital clasped thumb.